Eksperimental Variasi Perbandingan Putaran Mata Pisau Pengantar Terhadap Hasil Pengupasan Mesin Pengupas Sabut Kelapa - Angga Septiawan; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In the handling of agricultural products, peeling and cutting are a job that has always been done since harvesting until the product is ready to be consumed or processed further.The simple peeling and cutting jobs can be completed manually using a knife or other cutting tool. However, if the amount of peeling coconuts at harvest is large in numbers, manually requires considerable time and labor. Currently design a coconut peeling machine using screw feeding system, which equipped a peeling knife and spike roller. This research proposed to improve the machine performance designed with investigated the variation of peeler blade rotation. The method used in this research was an experimental testing by varying the rotation of the peeler blade (peeling knife and spike roller) and two rollers for forced rotation. Then, the coconut peeling results (coconut husking) were compared and analyses. After testing the rotation of variation of peeling blade and companion blade of coconut peeling machine, that was resulted good husk for 3 of 8 of coconut stripping, which rotation of peeling blade and companion blade of 20 rpm and 15 rpm respectively. These peeling results became better for 3 coconuts due to distance two roller of peeling knifes that whas set up on 175 mm.Keywords: Coconut peeling machine, Blade, Round Variation, Peeling result.